A model‐based approach using GSK3772847, an anti‐interleukin‐33 receptor monoclonal antibody, as a showcase to predict SC administration PK and free target dynamics based on PK and total target measurements after IV administration - Jan Berkhout; Dave Fairman; Martijn vanNoort; Tamara J. vanSteeg (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Integrated modeling of the pharmacokinetic (PK) and target binding, by means of a TMDD model, can provide valuable insights into the expected pharmacodynamic (PD) effects of monoclonal antibodies (mAbs). Optimal characterization of the human PK and target binding for mAbs requires data obtained after intravenous (IV) administration which can be combined with subcutaneous (SC) data to further this characterization. Integration of free and/or total target measurements in a population TMDD model will allow quantification of target engagement which is the first step in the cascade leading to efficacy. However, the assays for determination of free target concentrations are analytically challenging and are inherently biased to overpredict the true concentrations in the presence of mAb:target complexes. For that reason, the objective of the current research was to evaluate the predictive value of free target concentrations in a TMDD model developed using PK and total target observations only. Further, a secondary objective was to demonstrate that prediction of SC data is feasible, based on an existing IV model and typical values of mAb parameters reported for SC absorption. GSK3772847, a human immunoglobulin G2 sigma isotype (IgG2f) mAb that binds to the extracellular domain of the interleukin‐33 receptor (IL‐33R or ST2) and neutralizes IL‐33‐mediated ST2 signaling, was used as a model compound for mAbs in this study.